Movement and Metabolism of Kinetin-(14)C and of Adenine-(14)C in Coleus Petiole Segments of Increasing Age - Veen, Henk (1969)
To see if polar movement was typical of growth-regulators other than auxins, the movement of adenine-8-(14)C and of kinetin-8-(14)C was studied in segments cut from petioles of increasing age. No polarity was found. In time-course experiments lasting 24 hr, kinetin showed a progressive increase of radioactivity in receiver blocks, while adenine showed a maximum at 8 hr with a decline thereafter. More kinetin moved through older segments than through younger ones. There was no difference in net loss as far as the position of the donor block is concerned. However, the loss of radioactivity from adenine donor blocks was much higher than the loss of radioactivity from kinetin donor blocks. The radioactivity in receiver blocks after 24 hr treatment with kinetin-(14)C was still with kinetin, judging by location on chromatograms. By the same criterion, adenine and a smaller amount of some other compound were in receiver blocks after a 6 hr transport with adenine-(14)C in the donors. By contrast, more zones of radioactivity were extracted from petiole segments to which kinetin or adenine had been added. For both purine derivatives the original compound represented no more than 20% of the total radioactivity extracted from the tissue after a transport period of 24 hr.